Pengaruh Menopause Pada Wanita Umur 45-60 Terhadap Perubahan Body Image di Dusun Kawae Desa Maria Utara Kecamatan Wawo Kabupaten Bima Tahun 2019 - Nurwahidah Nurwahidah (Poltekkes Kemenkes Mataram, 2019)
Background: Menopause is the cessation of the menstrual cycle mainly due to the inability of the neurohumoral system to maintain its periodic stimulation of the endocrine system, baziad mentions menopause as the last uterine bleeding which is still managed by ovarian hormones. Objective: To determine the effect of menopause on women aged 45-60 to change body image in Kawae Hamlet, Maria Utara Village, Wawo District. Method: The design of this study used a descriptive analytic method with a cross sectional approach where the research was carried out by measuring or observing at the same time or once in a while between the independent variable and the dependent variable with a sample size of 28 respondents. The research instrument used was a questionnaire and analyzed data using the T test with a significant level ( = 0.00). Results: the study showed that respondents with menopause were 28 people (100%) and respondents who experienced a body image change of 19 people (67.9). The results of dialysis data with the T-Test p = 0,000 <value α 0.05 because the value of p = 0,000 <value α = 0.05 then it means that H0 is rejected Ha accepted.Conclusion: There is an effect of menopause on body image changes in women aged 45-60 in Kawae Hamlet, Maria Utara Village, Wawo District.